Perkembangan Industri Rumahan Batik Lebak Chanting Pradana di Desa Bojongleles Kecamatan Cibadak Kabupaten Lebak - Siti Saodah; Yuni Maryuni; Arif Permana Putra (Badan Riset dan Inovasi Nasional (BRIN), 2023)
Abstract The lack of public knowledge about batik Lebak often makes people less aware of its existence, because what is known is only batik Baduy. But between the two are two different things in the aspect of the motif and the meaning contained in it. Chanting Pradana Lebak batik home industry is one of the batik craftsmen in Lebak district that has produced various kinds of Lebak batik motifs. This study aims to discuss the history of the establishment and development of the Lebak Chanting Pradana batik home industry in Bojongleles Village, Cibadak District, Lebak Regency in 2015 - 2019. This research uses historical methods consisting of heuristics, source criticism, interpretation and historiography. The results showed that the Chanting Pradana industry was established in December 2015 and the first production on February 14, 2016, which was founded by Umsaroh. The motifs contained in Lebak batik have patterns, ornaments and socio-cultural characteristics of the people of Lebak Regency that reflect the life of the people of Lebak Regency. In the history of batik development in Lebak, the Lebak Government began launching 12 batik motifs that have obtained Intellectual Property Rights (IPR). In its development in 2015-2019, it has experienced the development of motifs, increased sales and the addition of the number of Human Resources (HR).